Closed form estimators for a multivariate gamma distribution. Issue 2 (4th March 2023) - Nawa, Victor Mooto; Nadarajah, Saralees
Abstract : Nawa and Nadarajah [Statistics, 2023, doi: 10.1080/02331888.2023.2168004 ] proposed closed form estimators for a bivariate gamma distribution. But these estimators do not have a direct multivariate extension. In this paper, we propose alternative closed form estimators with direct extensions to the trivariate and multivariate cases. These estimators can have smaller asymptotic variances and smaller asymptotic covariances compared to Zhao et al.'s estimators, method of moments estimators and Nawa and Nadarajah's estimators.